Kesesuaian teks dwibahasa Jawa-Indonesia jenjang B1 terhadap pedoman perjenjangan nomor 030/P/2022 - Mulasih, Mulasih; Suroso, Suroso; Efendi, Anwar (Universitas Mulawarman, 2025)
The need for children's literature that aligns with developmental stages and integrates cultural values is increasingly urgent to support contextual literacy. This study analyzes the alignment of manuscripts from the Ministry of Education's reading material competition with official leveling guidelines. Employing a qualitative approach with literature analysis, ten manuscripts from the 2023 Central Java Language Center competition were selected via purposive sampling. Analysis focused on three aspects: linguistics, content, and format. Regarding linguistics (complexity, organization, style, and predictability), most manuscripts complied, yet issues in structural complexity and organization weakened readability. In terms of content (genre, familiarity, and vocabulary), although genres were appropriate, rapid pacing and indistinct characters diminished developmental familiarity, while cultural vocabulary lacked explanation. Regarding format (length, typography, and layout), manuscript length was generally adequate, but inconsistencies in typography and illustration remained. The study concludes that the manuscripts fail to fully meet the leveling guidelines essential for child-friendly curation.